Kajian Manajemen Lalu Lintas di Stasiun Yang Melayani Kereta Kelas Ekonomi (Studi Kasus : Stasiun Lempuyangan Yogyakarta) - Suliyanti, Rini (Warta Penelitian Perhubungan, 2011)
The station is a node as the place to substitue mode of transport; therefore, the traffic in front of the station must be able to ensure the comfort and safety of users of the station. The traffic in front of the station must be able to ensure the comfort and safety of users of the station. Lempuyangan stations pass over by some type of economic train such as Logaya, Frago, Kahuripan, Night Train South Gayabaru, Bengawan, Pasundan, and Sri Tanjung. This study aimed to determine the condition of traffic in front of Lempuyangan station in Yogyakarta as one of the train station for economy class. In order to organize the traffic in front of the station that can be well integrated. From the analysis using SPSS 17.0 software and Microsoft Excel acquired a picture of the number of passengers using the station Lempuyangan increased by approximately 20% each year. While the average total daily passengers in the station's Lempuyangan number 2800 in 2010. At the peak hours there are 3310 pcu vehicles passing over the street in front of Lempuyangan Station. Based on the degree of traffic saturation which reached 1.37 in the area in front of the station Lempuyangan, it can be concluded that traffic conditions during peak hours with the release side friction along the station area is very crowded and reach over its traffic saturation, therefore traffic management and regulation are needed.Keywords: Management, traffic, Station Lempuyangan